Building an indigenous evidence-base for tribally-led habitat conservation policies. (December 2015) - Gadamus, Lily; Raymond-Yakoubian, Julie; Ashenfelter, Roy; Ahmasuk, Austin; Metcalf, Vera; Noongwook, George
Abstract: Habitat conservation is a priority for many tribes, and indigenous local experts develop environmental policy goals based on their traditional knowledge of animal habitat use and habitat change. An indigenous evidence-base for ice seal and walrus habitat conservation in the Bering Strait region of Alaska was built by using qualitative methods to document the knowledge of 82 local expert seal and walrus hunters. Local experts produced detailed descriptions of seal and walrus habitat use and drivers of change in key habitat features, as well as policy goals based on indigenous evidence. These indigenous habitat policy goals are compared to U.S. government policies and differences are explored in terms of the indigenous evidence-base.